The Use of Project-Based Learning Technology in the Process of Independent Language Learning of University Students - R. Sagitova, Rimma; A. Kharitonov, E; V. Fahrutdinova, Anastasiya (International Journal of Engineering and Technology, 2018)
The main task of Russian higher education is to prepare young people for independent improvement of their knowledge, create aspiration and readiness for continuous self-education and equip them with necessary skills. To provide the conscious approach in studentsâ€™ independent foreign language learning and to create an effective motivation for it, it is necessary to use project-based learning technology in the process of language learning. Project-based learning technology helps students to improve their skills in four types of speech activities â€“ reading and listening at the initial stages of the project work, speaking and writing interviews at subsequent stages of the project work. The main aim of the represented work is to study the effectiveness of using project-based learning technology in the process of independent foreign language learning of university students. The authors give different approaches to the definition of educational technology, reveal the concept of project-based learning technology in independent language learning, distinguish three main stages of project creating (design, technological and productive stages). The results and conclusions of the research can be used by teachers and lecturers at the English classes, seminars and in such lecture courses as â€œTechnologies of foreign language teaching in primary schoolsÂ»â€, â€œTheory of foreign language teachingâ€.Â Â